Penerapan Model Pembelajaran IPS Inside Outside Circle Berbantuan Power Point Interaktif - Wovie Azizah; Lucy Arsi Purwasih; Aren Frima (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the social studies learning outcomes of fifth grade students at SD Negeri 72 Lubuklinggau after the Inside Outside Circle Power Point Interaktif learning model has been applied significantly. This research method uses experimental research methods with pre-test and post-test experimental designs. Sampling was taken from the total population considering that there was only one class of the population, the population was the sample in this study, namely fifth grade students, totaling 24 students. The instrument used by the researcher was in the form of essay questions which totaled 8 questions. Data collection is taken by test technique. Data analyzed using the